Chinese Baijiu: The Perfect Works of Microorganisms - Tu, Wenying; Cao, Xiaonian; Cheng, Jie; Li, Lijiao; Zhang, Ting; Wu, Qian; Xiang, Peng; Shen, Caihong; Li, Qiang (Frontiers in Microbiology, 2022)
Chinese baijiu is a distilled liquor with a unique aroma that is made by mixing different grains in an open environment through the solid-state fermentation processes of jiuqu making and baijiu making. Chinese baijiu can be divided into different types according to the production area, production process, starter type, and product flavor. Chinese baijiu contains rich flavor components, such as esters and organic acids. The formation of these flavor substances is inseparable from the metabolism and interaction of different microorganisms, and thus, microorganisms play a leading role in the fermentation process of Chinese baijiu. Bacteria, yeasts, and molds are the microorganisms involved in the brewing process of Chinese baijiu, and they originate from various sources, such as the production environment, production workers, and Jiuqu. This article reviews the typical flavor substances of different types of Chinese baijiu, the types of microorganisms involved in the brewing process, and their functions. Methods that use microbial technology to enhance the flavor of baijiu, and for detecting flavor substances in baijiu were also introduced. This review systematically summarizes the role and application of Chinese baijiu flavor components and microorganisms in baijiu brewing and provides data support for understanding Chinese baijiu and further improving its quality.